Outcomes of Patients With Acute Low Back Pain Stratified by the STarT Back Screening Tool: Secondary Analysis of a Randomized Trial - Magel, John (Phys Ther, 2017)
BACKGROUND: The impact of physical therapy on the outcomes of patients with acute low back pain (LBP) stratified by the STart Back Screening Tool (SBST) is unclear. OBJECTIVE: The purpose of this study was to compare the outcomes of patients with acute LBP who were stratified as medium or high risk. DESIGN: This was a secondary analysis of a randomized trial. SETTING: Patients were recruited between March 2011 and November 2013 from primary care clinics in Salt Lake City, Utah. PARTICIPANTS: One hundred eighty-one participants with acute LBP who were stratified as medium risk (n = 120) or high risk (n = 61) by the SBST were included. They were aged 18 through 60 years, with duration of symptoms less than 16 days, no symptoms below the knee, no treatment for LBP in the past 6 months, and an Oswestry Disability Index (ODI) score of 20% or greater. INTERVENTION: After participants received education on how to manage their LBP, they were randomized to receive usual care (n = 97) by their primary care provider or early intervention (n = 84) by a physical therapist. MEASUREMENTS: The primary (3-month ODI score) outcome measure was obtained at baseline and at 4 weeks, 3 months, and 1 year. RESULTS: No differences were detected in the effect of intervention between participants stratified as medium or high risk. For the high-risk subgroup, there was a significant difference between the early intervention and usual care groups for the 3-month ODI (mean difference = –5.87 [95% CI = –11.24, –0.50]) favoring early intervention. LIMITATIONS: The primary study was not designed to examine the SBST. CONCLUSIONS: Patients with acute LBP stratified as high risk seem likely to respond well to one session of education. They may experience additional benefit by 3 months from evidence-based physical therapy treatments. These effects disappear at 1 year.